Lost in haze : evoking appreciation for environmental awareness through concept art : an exegesis presented in partial fulfilment of requirements for the degree of the Master of Design at the College of Creative Arts, Massey University, Wellington, New Zealand - Liu, Can (Massey University, 2017)
The levels of air pollution in many of Asia’s large cities and urban areas have exceeded the standards set by the World Health Organization (WHO) and National Ambient Air Quality Standards (NAAQS) (Oanh, 2012). In the northern part of China, the region of Shandong province that I come from, air pollution has become one of the most concerning issues for people. Moreover, the International Cancer Research Agency (IARC) has classified the polluting haze as a carcinogen (WHO, 2015) with harmful effects on human health, so this issue can no longer be ignored. In this design research project, I combine my personal experience of living in a city affected by air pollution, with my experience of visiting Tibet and experiencing its clear air and attractive vistas. Within the paradigm of graphic design, using applied visual psychology theory, interactivity theory, and a comparative analysis of key literary texts, I build a case for using concept art to produce scene designs that illustrate the effect of increased air pollution in China. I explain how perspective and colour are core to the design and artwork in order to engage and illustrate the impact of air pollution for the viewer. I argue that through the concept art created for a hypothesized fantasy story I can stimulate awareness and understanding of this far-reaching problem.
Keywords: Utopias in art; Graphic arts; Video games; Concept art; Environmental awareness; Visual psychology; Utopia; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects